Institutionalizing Speech Communication at the University of the Philippines Epistemic and Embodied Practices of a Disciplinary Formation - Serquiña, Oscar Tantoco, Jr. (2024)
Using a range of archival materials, this article chronicles the epistemic and embodied practices that came about during the establishment of the Department of Speech Communication and Theatre Arts (or DSCTA, formerly known as the Department of Speech and Drama) at the University of the Philippines Diliman in 1959. It examines these traditions of thought and action to explain the persistence of speech communication as a disciplinary formation in the Philippines; the role of the DSCTA in perpetuating various speech-related concepts, acts, and ideologies; and the importance of historicizing the knowledge systems governing how speeches and speakers came to be in the Philippines.
Keywords: Speech communication; Higher education; Curriculum planning (Higher education); Curriculum development; Curriculum; University of the Philippines